Effect of vitamin E on arginase activity in the liver and kidneys of testosterone-treated and castrated rabbits - Erisir, M; Aydilek, N; Aksakal, M (Veterinarni A Farmaceuticka Univerzita Brno, 2005)
In the present study we examined the effect of vitamin E administration on arginase activity in the liver and kidneys of testosterone-treated and castrated rabbits. Forty-six 3-month-old male rabbits were divided into six groups: 1) control rabbits, 0.5 ml olive oil; 2) testosterone-treated rabbits, 10 mg of testosterone propionate dissolved in 0.5 ml olive oil; 3) bilaterally castrated rabbits, 0.5 ml olive oil; 4) vitamin E-treated rabbits, 100 mg/kg dl-alpha-tocopheryl acetate dissolved in 0.5 ml olive oil; 5) vitamin E- and testosterone-treated rabbits, 100 mg/kg dl-a-tocopheryl acetate and 10 mg testosterone propionate dissolved in 0.5 ml olive oil; 6) bilaterally castrated and vitamin E-treated rabbits, 100 mg/kg dl-alpha-tocopheryl acetate dissolved in 0.5 ml olive oil. The administration was done subcutaneously over 24 h for 40 days; then the arginase activities in the liver and kidneys were determined. Liver arginase activities in all the groups did not change significantly (p > 0.05). Kidney arginase activities were not affected by castration and vitamin E. Kidney arginase activity was found to have increased two-fold by testosterone treatment. Testosterone-induced arginase activity in the kidneys returned to normal level with a significant lowering effect of the combination of vitamin E and testosterone. These results indicate that vitamin E supplementation has a significant reducing effect on the testosterone-induced arginase activity in the kidneys. Vitamin E ameliorates the testosterone-induced arginase activity in the kidneys.
Keywords: arginase; testosterone; castration; vitamin E